A study among dental students regarding the factors influenced dental students to choose dentistry as career - Gobichetti Palayam Jagatheeswaran AnbuSelvan; Subramaniam Gokulnathan; Vilvanathan PrabuRajan; Gangadharan RajaRaman; Singaravelu Suresh Kumar; Arthie Thagavelu (Wolters Kluwer Medknow Publications, 2013)
Introduction: Career choice is a complex decision for students since it determines the kind of profession that they intend to pursue in life. As students try to make a career choice while in secondary school, they face the problem of matching their career choices with their abilities and school performance. Aims: The purpose of this study was to examine factors influencing career choice among dental college students in private dental collages in Tamil Nadu, India. Settings and Design: The study was conducted using descriptive survey design with a population of 989 students. The data for this study was collected using a questionnaire and interview schedules. Materials and Methods: The data for this study was collected using questionnaire previously used by Swati Shah and Rajaraman and interview schedules. The analysis of the study was based on the factors: Outcome expectations, gender, personal interests, and other factors. Results and Conclusion: The most common reason for among the dental students to choose dental science as their career choice was self-interested followed by didn't get medicine degree, prestige and gives respect. The least common reasons observed in the study population were inspired by dentists. The findings of this study indicate that availability the most influential factors affecting career choices among students.